Resistência genética e indução de resistência no manejo da mancha aureolada e isolamento de fitobactérias - Martins, Stéfanny Araújo (2018)
The bacterial blight in coffee, etiological agent Pseudomonas syringae pv garcae, is responsible for significant losses in nurseries and crops, when under favorable conditions. Considering the need to manage this disease, the objective of this study was to evaluate the behavior of coffee progenies as to the level of resistance to the bacterial halo blight, to obtain a biochemical marker for the resistance, to elucidate the coffee mechanisms related to this disease defense, to find treatments inducers of resistance to this disease and to obtain a new protocol for the isolation of phytobacteria. Among the studied population, progeny UFV 7158 was the most promising for resistance to Pseudomonas syringae pv garcae. After this study, the expression of three defense genes with and without the presence of the pathogen were analyzed in both the cultivar used as a susceptibility standard (Mundo Novo 763/4) and in the UFV progeny 7158. The results obtained demonstrated that the levels of transcripts of the PAL gene in the seedlings inoculated with the bacterium were different in the two genetic materials. In the susceptible cultivar, there was a difference in the expression of this gene in the inoculated one in relation to the non inoculated, and this occurred 48 hours after exposure to the pathogen, while in the selected progeny with low incidence of the disease, this expression occurred more quickly after 12 hours of exposure to the pathogen. Parallel to the study of gene expression, a study on the quantification of bioactives in leaves of coffee trees with different levels of resistance to the aureolated spot was carried out. It was always possible to observe that when the cultivar or progeny had some resistance, the levels of chlorogenic acid increased in the leaf. Therefore, chlorogenic acid can be used as a biochemical marker for this disease. Regarding the induction of resistance, the results showed that some treatments were able to significantly reduce the disease by up to 90% when the plants were treated preventively and could thus be used in the integrated management of this disease. Regarding the bacteria’s isolation, it was possible to observe that the N-acetylcysteine molecule reduces the formation of bacterial biofilms inside the plant tissue, and that this result can be increased when using enzymes and ultrasound, obtaining up to twice the cells released viable when compared to the standard isolation protocol.